Popularitas Moderasi Beragama: Sebuah Kajian terhadap Tren Penelusuran Warganet Indonesia - Rahmatullah Rahmatullah (IAIN Palangka Raya, 2021)
Many activities have been carried out in the discourse of religious moderation on the internet. However, the activity of netizens search for information on the topic of religious moderation on the internet itself is still not well mapped. This paper aims to discuss trends in netizen search activities for information on the topic of religious moderation on the internet. The main data is sourced from Google Trends, which is focused on the period from December 2019 - December 2020. Data collection is done through documentation techniques. The data analysis process begins with restating the data that has been collected, then describes it, and finally the data interpretation stage is carried out. The result is that information search activities on the topic of religious moderation on the internet have not yet received massive search interest and a rich diversity of topics. The trend of searching for information on the topic of religious moderation on the internet has not yet reached high interest and is still not prevalent throughout Indonesia. This condition implies that efforts to promote the idea of religious moderation on the internet still need to be echoed again. The method used to build public attention to the topic of religious moderation cannot only be limited through the production of narratives or content about religious moderation in online media, but also needs to involve well-known figures who have high charismatics in the public sphere to build public attention. to be interested to browse and learn moderate religious knowledge on the internet.Keywords: Religious Moderation; Netizen; Internet